-6sin(9t)+3cos(9t)=0

Simple and best practice solution for -6sin(9t)+3cos(9t)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6sin(9t)+3cos(9t)=0 equation:


Simplifying
-6sin(9t) + 3cos(9t) = 0

Remove parenthesis around (9t)
-6ins * 9t + 3cos(9t) = 0

Reorder the terms for easier multiplication:
-6 * 9ins * t + 3cos(9t) = 0

Multiply -6 * 9
-54ins * t + 3cos(9t) = 0

Multiply ins * t
-54inst + 3cos(9t) = 0

Remove parenthesis around (9t)
-54inst + 3cos * 9t = 0

Reorder the terms for easier multiplication:
-54inst + 3 * 9cos * t = 0

Multiply 3 * 9
-54inst + 27cos * t = 0

Multiply cos * t
-54inst + 27cost = 0

Reorder the terms:
27cost + -54inst = 0

Solving
27cost + -54inst = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '54inst' to each side of the equation.
27cost + -54inst + 54inst = 0 + 54inst

Combine like terms: -54inst + 54inst = 0
27cost + 0 = 0 + 54inst
27cost = 0 + 54inst
Remove the zero:
27cost = 54inst

Divide each side by '27ost'.
c = 2ino-1

Simplifying
c = 2ino-1

See similar equations:

| -sin(9t)+3cos(9t)=0 | | 9x-1+4x=8x-7 | | 10-5(x-1)=5-x | | 2(3r+5)=-5(-4-2r)-6r | | P^2-2p-15= | | 0.5(k-5)=3 | | 6(1-n)=6n+1 | | 7x+1=2x-29 | | x*5+x=90 | | 2+6x=5x+7 | | 6x+6+4x=16 | | X+2=52-4x | | 2n^2+6n+8=0 | | 3x+12+2x+13=180 | | (7a-2)-(-3a+1)=-3(1-3a) | | z^2=-144 | | -2*(-2)= | | 2x+20+4x+10=180 | | 3x-7=79-3x | | 2.1x+49.6=15.4-9.3x | | 2*N*4=40 | | 8t-10=-18+6t | | yx=10 | | 8x-3=-57+2x | | 6*6+2y=12 | | 60+2x+3x=180 | | 15-b=a | | 4x=13x[]27 | | 6x+1=2x-19 | | 3(p-4)=8(p-4) | | D^2=-6d+27 | | 11x-4(x-5)=-22 |

Equations solver categories